The Effect of Business Intelligence and Intellectuals Capital of Company Value Moderated by Management of Profit Riil - Widhiastuti, Susanti; Murwaningsari, Etty; Mayangsari, Sekar (Journal of Accounting, Business and Finance Research, 2018)
The research purposes to analyze the influence of business intelligence and intellectual capital on firm value, and also the role of real earnings management as moderated variable. This research used annual report as secondary data. The number of beginning samples were 420 manufacturing firms. The final samples were 284 samples had a positive cash flow, because this study did not use samples with negative cash flow. This research uses moderated multiple regression and treat real earnings management as pure moderated variables. The results showed that business intelligence and intellectual capital had positive effects on firm value. Moreover, real earnings management significantly moderated the relationship between business intelligence, intellectual capital and firm value. The implication of the research showed that the company must give attention to business intelligence, intellectual capital and real earnings management. All independent variables can explain 86% of the variation in firms value.